Crop productivity and soil quality after fertilization with liquid swine manure - Tavanti, Renan Francisco Rimoldi [UNESP]; Da Silva Freddi, Onã; Tavanti, Tauan Rimoldi; Lorenzon, Kayane; De Morais dos Santos, Igor; Demicheli, Matheus; Costa, Letícia Carolina; Breda, Carlos Cesar (Universidad Nacional de Colombia, 2017)
An unresolved question about the use of animal waste in agriculture is its effect on the physical and chemical attributes of soil, especially in commercial grain producing areas that have adopted direct seeding system (DSS). Aiming at contributing to the clarification of this question, we conducted a study in the mid-north region of the Mato Grosso state, Brazil, in a soybean and maize commercial area consolidated in DSS. Different doses of liquid swine manure (LSM) were applied and compared with NPK mineral fertilization. The aim of this study was to evaluate the physical and chemical quality of the soil and the productive potential of the soybean and maize crops under LSM doses and NPK fertilizer. Results indicated an increase in levels of K, P, Zn and Cu exchangeable with LSM fertilization of 80 m3.ha-1. Fertilizers with mineral NPK and LSM at 80 and 60 m3.ha-1, respectively, show soil porosity improvements and decreased soil penetration resistance. Moreover, the use of LSM also provided the highest increases in soybean and maize grain yield.
Keywords: Direct sowing system; Fertilizers; Glycine max L; Soil fertility; Soil physics; Zea mays L